The role of digital technologies in the public administration sphere: El papel de las tecnologías digitales en el ámbito de la administración pública - Popova, Liubov; Seniv, Bohdan; Korol, Volodymyr; Galushko, Oleksandr; Biriukov, Iegor (Political Questions, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*113.39px); top: calc(var(–scale-factor)*245.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08296);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*136.31px); top: calc(var(–scale-factor)*245.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.11044);" role="presentation">article <span dir="ltr" style="left: calc(var(–scale-factor)*170.15px); top: calc(var(–scale-factor)*245.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08696);" role="presentation">is <span dir="ltr" style="left: calc(var(–scale-factor)*183.48px); top: calc(var(–scale-factor)*245.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.10392);" role="presentation">devoted <span dir="ltr" style="left: calc(var(–scale-factor)*224.52px); top: calc(var(–scale-factor)*245.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.13625);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*239.45px); top: calc(var(–scale-factor)*245.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09898);" role="presentation">highlighting <span dir="ltr" style="left: calc(var(–scale-factor)*299.28px); top: calc(var(–scale-factor)*245.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.15385);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*319.47px); top: calc(var(–scale-factor)*245.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.10482);" role="presentation">role <span dir="ltr" style="left: calc(var(–scale-factor)*342.73px); top: calc(var(–scale-factor)*245.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03721);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*357.46px); top: calc(var(–scale-factor)*245.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09703);" role="presentation">digital <span dir="ltr" style="left: calc(var(–scale-factor)*99.21px); top: calc(var(–scale-factor)*256.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.17999);" role="presentation">technologies in the public administration <span dir="ltr" style="left: calc(var(–scale-factor)*297.21px); top: calc(var(–scale-factor)*256.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.13448);" role="presentation">sphere<span dir="ltr" style="left: calc(var(–scale-factor)*326.83px); top: calc(var(–scale-factor)*256.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.22097);" role="presentation">, taking into <span dir="ltr" style="left: calc(var(–scale-factor)*99.21px); top: calc(var(–scale-factor)*267.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.11318);" role="presentation">account <span dir="ltr" style="left: calc(var(–scale-factor)*141.03px); top: calc(var(–scale-factor)*267.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.15385);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*162.34px); top: calc(var(–scale-factor)*267.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.13846);" role="presentation">modern <span dir="ltr" style="left: calc(var(–scale-factor)*204.32px); top: calc(var(–scale-factor)*267.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09827);" role="presentation">experience <span dir="ltr" style="left: calc(var(–scale-factor)*259.09px); top: calc(var(–scale-factor)*267.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03721);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*274.93px); top: calc(var(–scale-factor)*267.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.15385);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*296.25px); top: calc(var(–scale-factor)*267.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05701);" role="presentation">EU <span dir="ltr" style="left: calc(var(–scale-factor)*317.55px); top: calc(var(–scale-factor)*267.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.12155);" role="presentation">countries. <span dir="ltr" style="left: calc(var(–scale-factor)*368.67px); top: calc(var(–scale-factor)*267.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08296);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*99.21px); top: calc(var(–scale-factor)*278.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09311);" role="presentation">methodological basis of the research is the institutional approach, <span dir="ltr" style="left: calc(var(–scale-factor)*99.21px); top: calc(var(–scale-factor)*289.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.13366);" role="presentation">which provides for ensuring the effectiveness of the interaction <span dir="ltr" style="left: calc(var(–scale-factor)*99.21px); top: calc(var(–scale-factor)*300.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.20976);" role="presentation">between the components of the institutional system and the <span dir="ltr" style="left: calc(var(–scale-factor)*99.21px); top: calc(var(–scale-factor)*311.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.15938);" role="presentation">mechanisms of its implementation and control over the use of <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*322.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09998);" role="presentation">digital technologies and makes it possible to create an effective network of <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*333.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08944);" role="presentation">relationships between all levels of the system horizontally and vertically, as <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*344.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09794);" role="presentation">well as to increase the efficiency of the entire system public administration <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*355.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.13072);" role="presentation">and the quality of public services. The advantages of the implementation <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*366.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.17552);" role="presentation">of digital technologies in public administration are highlighted, which <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*377.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.07987);" role="presentation">makes it possible to: increase the efficiency of public administration, reduce <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*388.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.16752);" role="presentation">administrative costs, improve the quality of public services and ensure <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*399.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.17377);" role="presentation">their availability, and reduce the level of corruption. The results of the <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*410.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08209);" role="presentation">implementation of digitalization of public services in the EU countries were <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*421.83px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.1044);" role="presentation">analyzed in accordance with the program for the implementation of digital <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*96.44px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.12321);" role="presentation">measures within the framework of the Recovery and Sustainability Fund. <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*107.76px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0982);" role="presentation">The necessary directions for the activation of the implementation of digital <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*119.09px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.11343);" role="presentation">technologies in the public administration system are substantiated.